Reconstruction of the interplanetary magnetic field from the magnetosheath data: A steady-state approach - Toepfer, S.; Narita, Y.; Schmid, D. (Frontiers in Physics, 2022)
In the steady-state picture, the magnetic field can be formulated by a curl-free potential field in the magnetosheath region, and the sheath field is uniquely and linearly determined by the upstream field and the transformation matrix which contains the effect of field cancellation making the magnetospheric cavity. The curl-free sheath model can be used to reconstruct the upstream field for a given magnetic field data set in the magnetosheath region. The applicability and the limits are theoretically evaluated such that the reconstruction works reasonably as far as the sheath sampling position is not close to the magnetopause, and that the upstream field can be estimated within an error ranging from 10 to 40 percent, depending on the region of sampling.